Comparison of normal and distributed jet array impingement boiling of HFE-7000 on smooth and pin-fin surfaces. (November 2018) - Cui, F.L.; Hong, F.J.; Cheng, P.
Highlights: Bubble dynamics are compared for normal and distributed jet arrays on smooth or pin-fin surfaces. The thermal transfer performances of normal and distributed jet arrays are compared for smooth and pin fin surfaces, respectively. Better thermal transfer coefficient and higher CHF are acheived for the distributed jet arrays. The boiling instability is found in the late stage of nucleate boiling for the distributed jet arrays on pin fin surfaces. Abstract: The confined jet impingement boiling experiments are conducted with HFE-7000 as coolant to compare bubble dynamics and heat transfer characteristics of normal and distributed jet arrays on smooth surfaces and pin-fin surfaces, respectively. It is found that in single-phase regime, the two jet arrays have almost the same heat transfer coefficient (HTC) because of the negligible crossflow effect due to small jet velocities and short flow path. This is especially true on pin-fin surfaces owing to its further attenuation effect on crossflow. For each test section, the higher the flow rate is, the larger the single-phase coefficient (HTC) and critical heat flux (CHF) are, whereas the flow rate has negligible effect on HTC in fully developed nucleate boiling regimes due to the dominant role of nucleate boiling heat transfer. On smooth surfaces, nucleate boiling starts at the center of two jet rows for both jet arrays where the heat transfer is the weakest before boiling. Nevertheless, the wall superheat at the onset of nucleate boiling (ONB) for the distributed jet array is slightly lower under the same flow rate both on the smooth and pin-fin surfaces. For normal jet array, quantities of bubbles generated at high heat flux deteriorate the flow rate distribution and consequently results in the very different boiling characteristics along the streamwise direction. For distributed jet arrays, bubble characteristics are the same for each unit because of the absence of crossflow effect, and therefore its two-phase HTC and CHF are higher. This feature of distributed jet array makes it practical to large area cooling applications. Pin-fin surfaces can greatly decrease ONB, enhance HTC during whole heat transfer regimes and increase CHF for both jet arrays. Meanwhile, the boiling curves of the two jet arrays are overlapped in a wider range of two-phase regime due to the pin-fin enhancement on nucleate boiling and the attenuation of crossflow, while distributed jet arrays have much higher CHFs. For distributed jet arrays on pin-fin surfaces, boiling instability occurs at a certain range of heat flux owing to the periodical accumulation and extraction of large individual bubbles under effusion holes. The boiling instability, however, has no detrimental effect because it only leads to a slight drop in HTC and does not cause earlier occurrence of CHF.